Recent advances in triplet–triplet annihilation upconversion and singlet fission, towards solar energy applications. Issue 12 (10th November 2022) - Carrod, Andrew J.; Gray, Victor; Börjesson, Karl
Abstract : Here we consolidate recent advances in the fields of triplet–triplet annihilation photon upconversion and singlet fission. We further describe their utility in increasing the efficiency of photovoltaic devices. Abstract : Solar energy is an ample renewable energy resource, with photovoltaic (PV) technology enabling a direct route from light to electricity. Currently, PVs are limited in photon conversion efficiency, due in major part to spectral losses. Mitigation of these losses is therefore important, economically and environmentally. Two processes that aim to increase solar light utilisation are described herein. The first is triplet–triplet annihilation upconversion (TTA-UC), through which two incoherent photons of low energy can produce one of higher energy, reducing below bandgap losses. Secondly, singlet fission (SF), through which two triplet states may be obtained from one initial singlet excited state, in theory allowing two electrons per photon in a PV, reducing thermalisation losses. These fields are often covered seperately, despite being the reverse processes of one another. This work aims to consolidate research in the two fields and highlight their similarities and common challenges, specifically those relevant to PV applications. Herein, we cover systems primarily based on organic small molecules (anthracene, rubrene, tetracene, pentacene), and detail the fabrication of functional materials containing them (MOFs, gels, SAMs on TiO2, thin evaporated and solution cast films, and cavities). We further offer our recommendations for the focus of future work in both the TTA and SF fields, and discuss the need to address current limitations such as poor triplet diffusion, limited charge injection to PVs, and material stability. Specifically, one could do this by cherry picking ideas from other research fields, for example photosensitisers for photodynamic therapy could be used as TTA sensitisers, and molecules having a considerable excited state aromaticity could be considered as SF materials. We hope this review may aid development towards the end goal of an efficient PV, incorporating either, or both, SF and TTA-UC materials.